Indian Contribution in Immunology and Microbiology 1999-2008: A Scientometric Analysis - Kaur, Har; Gupta, B.M. (DESIDOC Journal of Library & Information Technology, 2010)
The study examines Indias performance based on its publication output in immunology and microbiology during 1999-2008, based on several parameters, including the countrys annual average growth rate, global publications share and rank, institutional profile of select top 15 institutions, international collaboration profile and major collaborative partners, patterns of communication in national and international journals, and characteristics of its top 15 most productive authors. The study uses 10 years publications data in immunology and microbiology drawn from Scopus international multidisciplinary bibliographical database. http://dx.doi.org/10.14429/djlit.29.268